SARS-CoV2 Viral Ct Values Correlation with Some Patients’ Factors and Disease Outcome - Hussein, Hussein Abdulsalam; Goreal, Amer Abdalla (Iraqi Journal of Science, 2024)
Viral load of COVID-19 can be concluded from the cycle threshold (Ct) values measured by RT-PCR test performed on suspected samples. SARS-CoV2 viral load has not been standardized yet to reflect the outcome of COVID-19 infection. This cross-sectional study was performed to detect the frequency of SARS-CoV2 among suspected patients and the correlation of viral RNA load represented by cycle threshold (Ct) values with patients’ clinical presentation (disease severity), comorbidities and demographic data.A total of 520 participants suspected to have SARS-CoV2 infection were enrolled. After filling a questionnaire, a nasopharyngeal swab was collected from each patient and subjected to RT-PCR with the use of specific primers. Ct values of positive cases were obtained.Results revealed that 277 (53.3%) of samples were positive by RT-PCR, of which 160 (57.8 %) were males and 117 (42.2 %) females, with mean Ct value being 27.43. There was no significant correlation of Ct values with different age groups, gender and comorbidities. However, higher Ct values (lower viral RNA load) were recorded in severe and critical patients, which was an interesting result.